Ribbed vaults of late Gothic in Sardinia - Casu, Paola; Pisu, Claudia (DISEGNARECON, 2012)
The late Gothic construction practice, settled in the Spanish Mediterranean area, is based on predetermined geometric rules and is shown in religious buildings with ribbed vaults. The proportion between the sides of the area to cover, tracing plan of the ribs as a succession of corner bisectors, stereotomy problems and volumetric aspects, are just some of the elements that can describe the complex construction of a ribbed vault . The aim of this paper is to analyze the dimensional information of the late gothic ribbed vaults of Sardinia, in order to define the geometric and proportional rules for a correct drawing, establishing a standard procedure for the collection of measures and the construction of the 3D model of vaults.